2022
DOI: 10.1002/bmc.5414
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analyses of Xiaopi granules in N‐methyl‐N′‐nitro‐N‐nitrosoguanidine–induced gastric epithelial dysplasia rat model using LC–MS

Abstract: Xiaopi granules have been shown to ameliorate gastric epithelial dysplasia in patients.However, the therapeutic mechanism is unclear. Herein, the proteomics method was applied to identify the differentially expressed proteins and related pathways. Sixty male Sprague-Dawley rats were randomly divided into four groups: control (C group, n = 10), model (M group), Xiaopi granules (X group), and vitacoenzyme (V group). The rat gastric epithelial dysplasia model was established by intragastrically administering N-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The findings of Cai et al (2019) implied that abnormal glycolysis induced by MNNG in gastric precancerous lesions in rats was relieved by Weipixiao decoction. Peng et al (2022) found that Xiaopi granules ameliorated MNNG mediates gastric epithelial dysplasia by intervening in metabolism, digestion, coagulation, and other related physiological/pathological processes. Dendrobium huoshanense polysaccharides might protect against MNNG-induced injury of gastric mucosa cells mediated by nicotinamide and energy metabolism related pathways ( Xie et al, 2023 ).…”
Section: Interventional Effect Of Phytochemicals On Mnng Induced Gast...mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of Cai et al (2019) implied that abnormal glycolysis induced by MNNG in gastric precancerous lesions in rats was relieved by Weipixiao decoction. Peng et al (2022) found that Xiaopi granules ameliorated MNNG mediates gastric epithelial dysplasia by intervening in metabolism, digestion, coagulation, and other related physiological/pathological processes. Dendrobium huoshanense polysaccharides might protect against MNNG-induced injury of gastric mucosa cells mediated by nicotinamide and energy metabolism related pathways ( Xie et al, 2023 ).…”
Section: Interventional Effect Of Phytochemicals On Mnng Induced Gast...mentioning
confidence: 99%
“…MNNG can induce gastric cancer by regulating inflammation, cell damage, cell differentiation mitochondrial dysfunction, glycolysis pathogenesis and oxidative stress processes ( Cai et al, 2018 ; Zhao et al, 2019a ; Cai et al, 2019 ; Cui et al, 2021 ; Wen et al, 2021 ; Gunes-Bayir et al, 2022 ). MNNG promotes the occurrence and development of gastric cancer by regulating processes such as autophagy, EMT, apoptosis, proliferation, angiogenesis, gastric epithelial dysplasia, malignant transformation and change endogenous metabolites ( Zhao et al, 2019b ; Deng et al, 2019 ; Wu and Hui, 2020 ; Liang et al, 2022a ; Cai et al, 2022 ; Chen et al, 2022 ; Peng et al, 2022 ; Yang et al, 2022 ; Xie et al, 2023 ).Therefore, there is an urgent need to find an effective and low side effect intervention or treatment strategy. In recent years, phytochemicals and active ingredients of herbal medicine have showed excellent application prospects in the prevention and treatment of gastric cancer.…”
Section: Effects Of N-nitrosamines and Mnng On The Occurrence And Pro...mentioning
confidence: 99%